Assessment of tuberculosis among male prisoners in Shiraz central prison, south of Iran. - Hossein Faramarzi; Razieh Sadat Mousavi-Roknabadi; Zahra Shayan; Ali Faramarzi; Sima Javanmard; Sadegh Kamgar (Shahid Beheshti University of Medical Sciences, 2021)
Background: Prisons play an important role in the prevalence of Tuberculosis (TB) in a region. This study aimed to determine the situation of TB in high-risk male prisoners in Shiraz central prison of Fars province in southern Iran. Methods: This cross-sectional study (June-October 2018) was conducted on male prisoners in Shiraz central prison, southern Iran. According to 4 criteria, the prisoners were determined as high-risk prisoners for TB, and para clinical tests included three sputum samples and chest radiograph were performed for them. Then, the high risk and low risk participants were compared in terms of demographic characteristics and past medical history. Results: Among 2,995 prisoners, only 108 (3.6%) had at least one of the high-risk criteria. But after performing further TB tests for these prisoners, no prisoners with TB disease were found. The high-risk prisoners were statistically older than low-risk prisoners (38.30±9.74 vs. 35.17±9.62, P=0.001). Also, the length of incarceration was statistically different in both groups (P=0.002), and drug abuse was more in high-risk group (P<0.001). Moreover, high risk prisoners used cigarettes/day more (14.87±11.55 vs. 9.71±9.09, P<0.001), but both groups were not different in term of the marital status (P=0.519), educational level (P=0.662), job (P=0.39), and nationality (P=0.342). Conclusion: Our results showed that none of the high-risk prisoners for TB had positive test. The length of incarceration, drug abuse, smoking, as well as age were more in high-risk prisoners in comparing low risk group.